A Most Masculine State : Gender, Politics and Religion in Saudi Arabia / [electronic resource] - Al-Rasheed, Madawi (Cambridge : Cambridge University Press, 2013)
Women in Saudi Arabia are often described as either victims of patriarchal religion and society or successful survivors of discrimination imposed on them by others. Madawi Al-Rasheed's new book goes beyond these conventional tropes to probe the historical, political and religious forces that have, across the years, delayed and thwarted their emancipation. The book demonstrates how, under the patronage of the state and its religious nationalism, women have become hostage to contradictory political projects that on the one hand demand female piety, and on the other hand encourage modernity. Drawing on state documents, media sources and interviews with women from across Saudi society, the book examines the intersection between gender, religion and politics to explain these contradictions and to show that, despite these restraints, vibrant debates on the question of women are opening up as the struggle for recognition and equality finally gets under way.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).